A Cluster-First Route-Second Heuristic Approach to Solve The Multi-Trip Periodic Vehicle Routing Problem - Annisa Kesy Garside; Nabila Rohmatul Laili (Jurnal Teknik Industri, 2019)
This paper discusses periodic vehicle routing problems that allow vehicles to travel on multiple trips in a single day. It is known as the Multi-Trip Periodic Vehicles (MTPVRP) Problem Route. Cluster-first route-second (CFRS) heuristics to solve MTPVRP was proposed in this study. In phase 1, customers were divided into clusters using the formulation of integer programming. Phase 2 determined the route of the cluster and verified that the total journey time to visit the trips does not exceed the working hours of the vehicle. Implementing the heuristic CFRS to solve the real problem faced by the  Liquefied petroleum gas (LPG) distributor shows that the procedure could provide a better routing solution.